Analysis Grammatical Errors in Using Simple Present Tense in Writing Descriptive Text - Zahro Salsabila; Muthia Mubasyira (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
One of the English skills which are important to be mastered by the students is writing skill. Writing is a creative and expressive process. Students need to explore their ideas and compose them into a good text. The objectives of this research are to find out types of error and the most dominant error writing using simple present tenses in a descriptive text.